P054 Pelvic Inflammatory Disease (PID) – Is telephone follow-up feasible, safe and effective?. (30th June 2016) - Lwin, Myat; Forsyth, Sophie; Daniel, Jessica; Hill, Laura
Abstract : Background: BASHH guidelines recommend follow up after PID treatment. A previous clinic audit highlighted high DNA rates for such appointments. In October 2013 we introduced a telephone follow-up protocol for PID to reduce unattended appointments without compromising patient safety and satisfaction. Patients diagnosed with PID were referred to the Health Advisor (HA) at the first consultation to commence the Partner Notification (PN) process. HA's then conducted a telephone follow-up appointment 2 weeks later to ensure treatment compliance and review symptoms. Aim: To audit the performance of the new PID telephone follow-up protocol and estimate number of appointments saved. Method: A 3 months retrospective electronic case note and PN record review of female patients diagnosed with C5A attending between 1/7/14 and 30/9/14. Results: 59 eligible case notes reviewed. Mean age = 25.8 years. 66% (39/59) patients received telephone follow-up. 71% (28/39) patients contacted on first attempt and all were happy to be telephoned. As per PID protocol 23% (14/59) patients with positive Chlamydia, gonorrhoea test or IUD in situ were advised to attend for doctor review. Of these 36% DNA'd their clinic follow up appointment. PN rates 0.8%. Discussion: PID follow up performed by HA telephone consultation is acceptable to patients and HCP's. We saved 39 doctors appointments over 3 months and there was no impact on PN rates or patient safety. Since this audit we now include patients with Chlamydia and IUD's in the telephone follow-up protocol, and men with Epididymo- orchitis. We estimate we could save 280 follow-up appointments a year.